2016
DOI: 10.1002/cbic.201600165
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Structural Analysis of New Nrf2 Activators by Mechanism‐Based Chemical Transformation of 15‐Deoxy‐Δ12, 14‐PGJ2

Abstract: Mechanism-based chemical transformation of 15-deoxy-Δ -PGJ (15d-PGJ ) resulted in a series of new NF-E2-related factor-2 (Nrf2) activators and detailed elucidation of the function of each electrophilic binding site. In addition, HO-1 expression resulting from Nrf2 activation through enhanced dissociation of the Keap1-Nrf2 complex by the new activators was proved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This moiety has been known to interact covalently with a cysteine residue of a target protein through Michael addition, resulting in alteration of the protein structure and function [7,8]. For instance, 15d-PGJ 2 was found to directly interact with thiol groups of the Keap1, a negative regulator of the redox-sensitive transcription factor Nrf2 [33]. Subsequent studies have shown that 15d-PGJ 2 covalently modifies IjB kinase and TrxR, thereby provoking intracellular oxidative stress and cell death [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This moiety has been known to interact covalently with a cysteine residue of a target protein through Michael addition, resulting in alteration of the protein structure and function [7,8]. For instance, 15d-PGJ 2 was found to directly interact with thiol groups of the Keap1, a negative regulator of the redox-sensitive transcription factor Nrf2 [33]. Subsequent studies have shown that 15d-PGJ 2 covalently modifies IjB kinase and TrxR, thereby provoking intracellular oxidative stress and cell death [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…15d-PGJ 2 was purchased from Cayman Chemical Co. (Ann Arbor, MI, USA). 15d-PGJ 2 analogues were synthesized as described previously [33]. Dulbecco's modified Eagle's medium (DMEM)/Ham's nutrient mixture F-12 (1 : 1) and horse serum was obtained from Gibco BRL (Grand Island, NY, USA).…”
Section: Methodsmentioning
confidence: 99%